2005
DOI: 10.1111/j.1365-294x.2005.02545.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of algal endosymbionts (zooxanthellae) in octocorals: the roles of geography and host relationships

Abstract: The presence, genetic identity and diversity of algal endosymbionts (Symbiodinium) in 114 species from 69 genera (20 families) of octocorals from the Great Barrier Reef (GBR), the far eastern Pacific (EP) and the Caribbean was examined, and patterns of the octocoral-algal symbiosis were compared with patterns in the host phylogeny. Genetic analyses of the zooxanthellae were based on ribosomal DNA internal transcribed spacer 1 (ITS1) region. In the GBR samples, Symbiodinium clades A and G were encountered with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
125
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(138 citation statements)
references
References 44 publications
12
125
1
Order By: Relevance
“…The evolution of coral hosts and their endosymbionts remains unclear. As an illustration, studying 69 genera (20 families) of octocorals and their endosymbionts, Van Oppen, Mieog, Sánchez, and Fabricius (2005) revealed that the symbiotic associations (at the level of phylogenetic clades) are not easily explained by taxonomic affiliation of the hosts. Nevertheless, host–symbiont association could be, on the contrary, more specific at the genus level.…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of coral hosts and their endosymbionts remains unclear. As an illustration, studying 69 genera (20 families) of octocorals and their endosymbionts, Van Oppen, Mieog, Sánchez, and Fabricius (2005) revealed that the symbiotic associations (at the level of phylogenetic clades) are not easily explained by taxonomic affiliation of the hosts. Nevertheless, host–symbiont association could be, on the contrary, more specific at the genus level.…”
Section: Discussionmentioning
confidence: 99%
“…The unique octocoral Heliopora coerulea, which has a rigid aragonitic skeleton similar to stony hexacorals, was also studied. Among the corals collected, 2 genera of stony corals (Balanophyllia and Tubastrea), 1 genus of alcyonarians (Dendronephthya), 6 genera of gorgonians (Annella, Melithaea, Parisis, Menella, Paracis, and Viminella), and Siphonogorgia were azooxanthellate; other genera contained zooxanthellae (Fabricius & Alderslade 2001, van Oppen et al 2005.…”
Section: Methodsmentioning
confidence: 99%
“…harboured a single Symbiodinium clade). It should however be noted that heteroplasmic colonies are not found in tropical octocorals either, even in places where significant Symbiodinium diversity exists (Van Oppen et al 2005). Whether the homoplasmic status of E. singularis is intrinsic to symbiotic octocorals or due to the apparent absence of an alternative symbiont in the Mediterranean is still an open question; but in any case this observation means that E. singularis appears to be homoplasmic, along with the vast majority of symbiotic cnidarians (Goulet 2006).…”
Section: Symbiont Genetic Diversitymentioning
confidence: 99%